A Highly Controlled Organic–Inorganic Encapsulation Nanocomposite with Versatile Features toward Wearable Device Applications. Issue 17 (6th August 2021) - Tang, Ruijie; Yao, Xiaoxue; Chen, Jingyi; Sridar, Sreepathy; He, Xianglei; Pu, Yuan; Wang, Jie‐Xin; Wang, Dan; Wang, Steven
Abstract: Ultraviolet‐curable polyurethane acrylate (PUA) materials can be used in a number of important applications spanning from microfluidics, surface patterning to wearable technology. For the first time, the potential of encapsulation of modified zirconia (ZrO2 ) nanoparticles is reported in PUA‐based hybrid films aimed to facilitate profoundly enhanced hardness and refractive index. By successfully manipulating the interfacial reaction conditions between ZrO2 nanoparticles and PUA film, the PUA‐based nanocomposites exhibit an ultrahigh hardness of 9 and superior refractive index of 1.64 (589.3 nm). The outcomes obtained pave the way for seamless application of nanozirconia/PUA as a potent encapsulating material that provides structurally morphable, water resistant, and optically transparent light emitting diodes toward wearables devices in healthcare. Abstract : An encapsulation of modified zirconia (ZrO2 ) nanoparticles in ultraviolet‐curable polyurethane acrylate‐based hybrid films is fabricated for wearable device applications, which have an ultrahigh hardness of 9 and an excellent refractive index of 1.64 (589.3 nm). The highly controlled material provides structurally morphable, water resistant, and optically transparent light emitting diodes toward wearables devices in healthcare.